Recurrent GRHL fusions in a subset of sebaceoma: microscopic and molecular characterisation of eight cases - Legrand, Mélanie; Louveau, Baptiste; Macagno, Nicolas; Mancini, Maxence; Kazakov, Dmitry V; Pissaloux, Daniel; Tirode, Franck; Tallet, Anne; Mourah, Samia; Lepiller, Quentin; de la Fouchardière, Arnaud; Sohier, Pierre; et al. (Histopathology, 2025)
Aims Sebaceous neoplasms constitute a group of adnexal tumours, including sebaceous adenoma, sebaceoma and sebaceous carcinoma. Although mismatch repair deficiency may be observed, the nature of the genetic alterations contributing to the development of most of these tumours is still unknown. In the present study, we describe the clinical, microscopic, and molecular features of eight sebaceomas with GRHL gene rearrangement. Methods and results Among these sebaceomas, four occurred in women and four in men; the median age was 63 years (range = 29-89). The tumours were located in the head and neck area in all cases. Microscopic examination revealed a well-demarcated lesion located in the dermis with focal extension into the subcutaneous tissue (three cases). The neoplasms displayed macronodular (eight cases), cribriform (seven cases) and organoid (six cases) growth patterns, occurring in combination. The tumours were mainly composed of immature basophilic cells associated with scattered mature sebocytes. Numerous small infundibular cysts were present in seven cases. Mitotic activity was low (none/one to four mitoses/mm2). Immunohistochemistry showed positivity for androgen receptor and p63. Preserved expression of MLH1, PMS2, MSH2 and MSH6 was observed in all cases. RNA-sequencing revealed RCOR1::GRHL2 (three cases), BCL6::GRHL1 (two cases), a BCOR::GRHL2 (one case), RCOR1::GRHL1 (one case) and TLE1::GRHL1 (one case) fusion transcript. Methylation analysis demonstrated that GRHL-fused sebaceomas form an independent cluster and highlight the proximity of such tumours with poromas with folliculo-sebaceous differentiation. Conclusions In conclusion, we report recurrent fusions of the GRHL genes in a distinctive subset of sebaceomas harbouring infundibulocystic differentiation, a frequent organoid growth pattern and lack of mismatch repair deficiency.
Online verfügbar: 20. November 2024
Gesehen am 04.06.2025